Potensi Ekstrak Batang Kayu Gempol (Nauclea orientalis L.) dalam Menghambat Pertumbuhan Bakteri: Potency of Gempol (Nauclea orientalis L.) Stem Extracts to Inhibiting Bacterial Growth - Ni Kadek Atmiyanti; Pasjan Satrimafitrah; Abd. Rahman Razak; Nov Irmawati Inda; Indriani; Dwi Juli Puspitasari (KOVALEN: Jurnal Riset Kimia, 2022)
The study of the potential of Gempol wood stem extract (Nauclea orientalis L.) with three solvent polarities has been exercised to determine the extract with a certain polarity and the smallest concentration that can inhibit the growth of bacteria Staphylococcus aureus and Escherichia coil. Extraction is performed using the maceration method with n-hexane, ethyl acetate, and ethanol as solvents. Furthermore, the potency in inhibiting the growth of bacteria was observed by the diffusion method with a range of extract concentrations from the largest to the smallest. The extract's ability to inhibit bacterial growth in the time range of up to 24 hours was measured using the turbidimetric method. The results showed that ethyl acetate and ethanol extracts were able to inhibit the growth of both bacteria in a wide concentration range (100 %– 5%), although n-hexane extracts showed the highest percentage in inhibiting both bacteria (15.27 mm and 16.89 mm, respectively). Turbidimetric assays showed the extract was stronger in inhibiting S. aureus compared to E. coli in the logarithmic phase range of 12 hours. This study showed that semipolar and polar extracts can inhibit the growth of bacteria with a wider concentration range compared to non-polar extracts despite having a higher inhibition capability.